Clinical Profile and Outcome of Dengue Fever in Tertiary Care Hospital at Kerala (Academia Journal of Medicine, 2020)
Background: Among all flaviviruses, Dengue is the most common fever. Every year 2-5 lakh cases of Dengue hemorrhagic fever occur. The objective of the study was to evaluate the clinical profile of patients with Dengue fever at a hospital in Kerala. Subjects and Methods: Patients with more than 12 years of age and those admitted with fever, headache, and myalgia were assessed with other clinical characteristics (warning signs of dengue fever, signs of hemorrhage, signs of plasma leakage and signs of shock). Laboratory examinations such as Hb, total count, differential count, platelet count, packed cell volume, peripheral smear for the malarial parasite, and liver function test (including S. protein) and renal function test were carried out. Blood coagulation profiles such as Bleeding Time, Clotting Time, Prothrombin Time and aPTT were performed. Radiological findings like X-ray chest and USG abdomen were also performed. Results: Consequently dengue fever is ordinary in young adults. In the current study, males were more pretentious than females. Males were affected by 63.7% while females are affected by 36.3%. The most usual indication was fever (94.8%) experienced in all patients followed by headache (41.3%), Generalized weakness (77.5%), myalgia (51.7%), vomiting (57.7%). Predominant organ involvement was hepatic (transaminases, jaundice) followed by gastrointestinal (abdominal pain, distension, loose stools, vomiting, ascites) systems. The total survivors are 86(74.1%) whereas 30(25.8%) were non-survivors. Conclusion: Dengue fever usually affects male and young populace. Headache, fever, myalgia are ordinary at hand grumble however in the recent few years, the world has observed the diverse experimental appearance of the dengue fever in dissimilar epidemics, even in the same regions and even with the period of times.
Keywords: Dengue Fever; Flaviviruses; Hemorrhagic Fever